Impact of Work Environment on Employee Productivity in Shipyard Manufacturing Company - Adi Irawan Setiyanto; Natalia Natalia (Journal of Applied Accounting and Taxation, 2017)
This study aims to determine the impact of working environment on employees’ productivity. This study took place in shipyard manufacturing company. Samples in this study of 315 respondents used quantitative approach with questionnaires method by using simple random sampling technique. The analysis technique applied multiple linear regression and the statistic test. The result indicates that either physical or non-physical working environment have positively and significantly impact with a contribution of 63.4% on employees’ productivity.